2018
DOI: 10.1101/495879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting phenotype using morphological cell responses to nanotopography

Abstract: AbstractCells respond in complex ways to topographies, making it challenging to identify a direct relationship between surface topography and cell response. A key problem is the lack of informative representations of topographical parameters that translate directly into biological properties. Here, we present a platform to relate the effects of nanotopography on morphology to function. This platform utilizes the ‘morphome’, a multivariate dataset containing single cell measures… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Incorporating a range of parameters, e.g., systematically changing geometry or testing multiple cell lines, into the experimental design can help. Approaches such as image‐based cell profiling can help to quantitatively analyze large numbers of cells, adding statistical weight to conclusions, as well as in identifying subpopulations and other effects driven by cell heterogeneity . For example, Reynolds et al illustrated the potential of these approaches for exploring the impact of topography in endothelial/fibroblast cell cocultures, in this case with low aspect ratio nanodot arrays ( Figure ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating a range of parameters, e.g., systematically changing geometry or testing multiple cell lines, into the experimental design can help. Approaches such as image‐based cell profiling can help to quantitatively analyze large numbers of cells, adding statistical weight to conclusions, as well as in identifying subpopulations and other effects driven by cell heterogeneity . For example, Reynolds et al illustrated the potential of these approaches for exploring the impact of topography in endothelial/fibroblast cell cocultures, in this case with low aspect ratio nanodot arrays ( Figure ) .…”
Section: Discussionmentioning
confidence: 99%
“…Approaches such as image-based cell profiling can help to quantitatively analyze large numbers of cells, adding statistical weight to conclusions, as well as in identifying subpopulations and other effects driven by cell heterogeneity. [137,173,263,459,460] For example, Reynolds et al illustrated the potential of these approaches for exploring the impact of topography in endothelial/fibroblast cell cocultures, in this case with low aspect ratio nanodot arrays (Figure 29). [263] Likewise, super-resolution microscopy techniques are likely to continue to offer better visualization of transmembrane proteins and interaction sites.…”
Section: Fundamental Challengesmentioning
confidence: 99%
“…While it is well-established that changes to gene expressions over a period of about 1-2 weeks dictate the lineage commitment and differentiation fate of hMSCs, more recent studies have indicated that a combination of a large number of cell, nuclear and cytoskeletal morphometrics also provides excellent forecasting of the lineage of hMSCs [22,23]. These morphometrics develop over a period of 1 to 2 days when the gene expression of cells has not been affected irreversibly by the environment.…”
Section: Modellingmentioning
confidence: 99%
“…A combination of a large number of cell, nuclear and cytoskeletal morphometrics that develop over a period of 1-2 days have been shown to forecast the lineage of hMSCs as measured via gene expressions over a period of about 1 week [22,23]. While such a morphometric analysis is undoubtedly useful it has two drawbacks: (i) it requires the measurement and analysis of a large number of morphological metrics, and (ii) it provides little insight into the physical phenomena that set the lineage of the cell.…”
Section: Early Forecasting Of the Lineage Of Hmscsmentioning
confidence: 99%
See 1 more Smart Citation